The role of herpes-virus infection and mixed infection in atopy - L. M. Ogorodova; O. V. Kozina (Бюллетень сибирской медицины)
An observative study of infectionary risk factors (simple herpes virus, toxoplasm, cytomatagalovirus, helminths, candida, staphylocoque, listeriosis) in reagine immunopathological reactions development has been undertaken in a basic group of 3183 patients. In the study the «case-control» method of populate investigation was being used. The patients of representative sample (293 persons) with atopic diseases have been investigated for specific antibodies for these diseases and IgE antibodies. The study results in a statistically trustworthy association between the simple herpes infection, cytomatagalovirus, helminths and candida infections, the IgE hyperproduction, and a numeral increase both of patients with combined forms of atopy and of accompanying diseases. The aforesaid makes us refer these infections to the risk factors causing infavourable development of atopic diseases. In the contrary, helminths infection in atopic patients correlates with decrease of IgE production that in general approves the so-called «hygienic hypothesis».